1987
DOI: 10.1016/0035-9203(87)90414-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania donovani soluble antigen and antibody in the urine of visceral leishmaniasis patients

Abstract: Urine samples from 21 patients with visceral leishmaniasis were examined for the presence of Leishmania donovani soluble antigen and antibody by double counter-current immunoelectrophoresis. 19 samples revealed both antigen and antibody (IgM in 5 and IgG in all samples). 2 urine samples collected 10 and 13 days after Glucantime treatment revealed only antibody (IgG), not soluble antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Using Western blot, Kohanteb et al [14] in 1987 performed a study of the urine of patients with leishmaniasis, in which they described the presence of mainly IgG, and to a lesser degree IgA. Similarly to our study, Kohanteb et al [14] found IgA exclusively in samples in which IgG was also found. In the present study, 13/15 dogs that showed IgG displayed signs of renal failure that would explain the passage of this immunoglobulin across the glomerular filtration barrier.…”
Section: Discussionsupporting
confidence: 85%
“…Using Western blot, Kohanteb et al [14] in 1987 performed a study of the urine of patients with leishmaniasis, in which they described the presence of mainly IgG, and to a lesser degree IgA. Similarly to our study, Kohanteb et al [14] found IgA exclusively in samples in which IgG was also found. In the present study, 13/15 dogs that showed IgG displayed signs of renal failure that would explain the passage of this immunoglobulin across the glomerular filtration barrier.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, several infectious diseases are diagnosed by the finding of specific antibodies in urine, such as Helicobacter pylori infection (18), filariasis (17), or schistosomiasis (35). The presence of anti-Leishmania antibodies in the urine of human patients with visceral leishmaniasis (16,20) and in the urine of L. donovani-infected hamsters (34) has also been described. In contrast, there is a lack of information about immunoglobulins in the urine of healthy and sick dogs.…”
Section: Discussionmentioning
confidence: 99%
“…All positive samples (urine and serum samples) recognized numerous polypeptide fractions of the L. infantum antigen with masses ranging from 12 to 85 kDa, with most bands at 16 to 69 kDa. The most frequent polypeptide fractions observed in both urine and serum samples were those of 14,16,20,30,31,48, and 69 kDa. The immunoblot analysis did not reveal any polypeptide fractions of the L. infantum antigen in ELISA-negative urine samples.…”
Section: Detection Of Anti-leishmania Antibodies In Urine Samples By mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these problems may be avoided by searching for antigens in the urine. Several studies have demonstrated Leishmania antigens in the urine of VL patients and animals using different techniques including double countercurrent immunoelectrophoresis (22), ELISA (3,20,36), and Western blotting (13). Recently, a latex agglutination test (KAtex kit) to detect Leishmania antigen in urine showed 100% specificity and 47 to 100% sensitivity in different studies with immunocompetent patients (2,32) and 96 to 100% specificity and 85 to 100% sensitivity in immunodepressed patients (31,37).…”
mentioning
confidence: 99%